First record of the smoky bat Furipterus horrens (F. Cuvier, 1828) (Mammalia: Chiroptera) in the state of Espírito Santo, southeastern Brazil - Rafaela Duda; Jeronymo Dalapicolla; Leonora Costa (Check List, 2012)
Furipterus horrens has its distribution restricted to the Neotropics. In the coastal states of Southeastern Brazil covered by Atlantic Forest, few records are known and the Espírito Santo state has never been included as an area of occurrence of the species. Here, we report the collection and identification, using morphological and molecular data, of a single individual from Floresta Nacional do Rio Preto, Conceição da Barra, which is the first record in Espírito Santo and fills in a gap in the known geographical distribution of this bat in the Atlantic Forest.